63.6k views
13 votes
Make x the subject of these equations.

a(x + b) = c
X =

User Fpmurphy
by
5.0k points

2 Answers

1 vote

Answer:

Just expand and solve for x :)

Make x the subject of these equations. a(x + b) = c X =-example-1
User Oivoodoo
by
5.3k points
10 votes

Answer:

x =
(c-ab)/(a)

Explanation:

a(x + b) = c ← distribute parenthesis on left side

ax + ab = c ( subtract ab from both sides )

ax = c - ab ( divide both sides by a )

x =
(c-ab)/(a)

User Charmi Gheewala
by
6.1k points